A financial analysis and life-cycle carbon emissions assessment of oil palm waste biochar exports from Indonesia for use in Australian broad-acre agriculture. Issue 2 (4th March 2018) - Robb, Samuel; Dargusch, Paul
ABSTRACT: Oil palm waste from South Sumatra may represent an abundant source of biochar for beneficial agronomic use in Australian broad-acre farming systems. Here a cost–benefit analysis and carbon footprint of biochar applied to three different Australian broad-acre crops are presented, covering application rates of between 1 and 40 Mg ha −1 and considering either the effect of the biochar on yield or the effect of the biochar on reduced fertilizer requirement. Yield and nutrient efficiency effects are assumed to be constant across all crops. Analysis reveals that empty fruit bunch biochar could be produced in South Sumatra and transported to the farm gate in Australia at a minimum acceptable sale price per Mg of USD $266 to the biochar manufacturer. Despite assumed uniformity of the biochar effect, the return on investment for the biochar user from the perspective of yield increase varied significantly by crop (sugarcane: 67% return on investment [ROI], irrigated cotton: 43% ROI, dry land cotton: −22% ROI, wheat: −72% ROI). The study found that the average carbon footprint in CO2 e over 100 years was −691 kg Mg −1 biochar when used to influence crop yield, and −286 kg Mg −1 biochar when used to reduce fertilizer requirements.